Phylogenetics of the freshwater crab (Potamonautes MacLeay, 1838) fauna from ‘sky islands’ in Mozambique with the description of a new species (Brachyura: Potamoidea: Potamonautidae) - Daniels, Savel R.; Bittencourt-Silva, Gabriela B.; Muianga, Vanessa; Bayliss, Julian (European Journal of Taxonomy, 2020)
Patterns and processes of cladogenesis among taxa living on the Mozambique ‘sky islands’ remain poorly studied. During the present study, we report on a new freshwater crab species from Mount Lico, an inselberg and ‘sky island’ in the Zambezia Province of Mozambique. Phylogenetic analyses using three mitochondrial DNA sequence loci (12S rRNA, 16S rRNA and COI) were used to determine the evolutionary placement of the freshwater crab specimens from Mount Lico. The freshwater crab specimens from Mount Lico were retrieved sister to Potamonautes choloensis. The new species, Potamonautes licoensis sp. nov., is described and compared with other southern African freshwater crab species. Divergence time estimations for the Mozambican freshwater crab species suggest a Miocene / Plio–Pleistocene diversification. Some endemic ‘sky island’ species form an early branching and are sister to other predominantly East African species, while other ‘sky island’ species are more recently derived and nested within a predominantly southern African clade. The present study presents the description of the fourth endemic freshwater crab species from Mozambique and suggests that the species diversity in the country is likely highly underrepresented, reiterating the call for renewed systematic surveys. An argument for the conservation of these mountainous ‘sky islands’ is presented.